INCIDENCE OF CERVICAL CANCER IN THE STATE OF PARAÍBA IN 2023 AND ITS CORRELATION WITH CYTOPATHOLOGICAL EXAMINATION - Costa, Amanda Santos Fernandes; de Aguiar, Claudiane Macedo Fernandes; Sousa, Eduardo Sérgio Soares; Pereira, Sibele Vieira; Cordeiro, Hartt Hindenburg Medeiros; de Barros, Davi Pereira Maurício; Gadelha, Clara Cristina Marques Teodoro de Figueiredo (Seven Editora, 2026)
Cervical cancer is caused by the Human Papillomavirus (HPV), although it is preventable through vaccination, especially serotypes 16 and 18, due to its virulence. This article aims to outline the epidemiological profile of cervical cancer in 2023 and its prospects. This is an exploratory, retrospective epidemiological study with a quantitative approach. The results were collected from data from INCA (National Cancer Institute), whose reports are issued biennially. A higher incidence was observed in the North and Northeast regions, with Paraíba accounting for 10.5% of cases and the Northeast 13.8% of cases. Cervical cancer detection is related to Pap smear or cytopathological testing, which should reach 100% of women aged 25 to 64, i.e., the most vulnerable population. The study resulted in a coverage rate of 83.23, and, because of its greater screening coverage, it has a lower cervical cancer mortality rate, since detection is linked to early treatment. It can be concluded that cervical cancer is a major public health problem; therefore, healthcare professionals should encourage patients to undergo this screening annually for early detection of HPV-related lesions and cancers.